Anatomical variation of intrahepatic biliary duct in cadaveric liver - Khatiwada, Sushma; Adhikari, Budhi Nath; Shrestha, Iju (Journal of Chitwan Medical College, 2019)
Background: Hepatobiliary system has many variations. Use of cadavers, intraoperative data and various imaging modalities are the commonly employed techniques for determining the anatomy of intrahepatic bile ducts. The vivid picture of hepatobiliary system is a must for hepatobiliary surgery and identification of frequency distribution of typical and atypical pattern and different types of atypical pattern are vital. This study aimed to uncover its frequency distribution and also to recognize the variations therein. Methods: An observational study was conducted in the Department of Anatomy, Kathmandu Medical College Teaching Hospital from July 2013 to June 2014 by taking 50 complete human cadaveric livers without evidence of injuries or previous operations. Livers were dissected, duct traced, colored, photographed and the findings were entered in a proforma. Results: Out of 50 dissected livers, 32 showed typical pattern (Type A, 64%) whereas 18 liver showed atypical pattern of confluence (36%). The type B pattern was seen in 6 (12%) and type C was seen in 8 of them (16%). Of these 8 cases, subtype C1 was observed in 6 livers (12%) and subtype C2 was found in 2 livers (4%). Type D was seen in 3 livers (6%). and all of them were of the subtype D1. There were no cases of subtype D2 and of type E. Type F was observed in a single case (2%). Conclusions: An accurate knowledge of the anatomical variations of the intrahepatic biliary tree is important for a successful hepatobiliay surgery.